2020
DOI: 10.1002/ceat.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Energy Storage Performances of Steel Slag‐Derived CaO‐Based Composites

Abstract: Low-cost and easily scaled-up acidification is a potential synthesis approach to produce CaO-based composites derived from steel slag for thermal energy storage/release via multicyclic calcination/carbonation. Acid concentration, acidification temperature, and acidification duration were comparatively investigated. The cyclic thermal energy storage/release properties of such composites are closely related to the acidification parameters, mainly attributed to the differences in the composition of the synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In the abovementioned acetic acid treatment process, a filtration step was added to remove silicon impurities, which could increase the effective conversion of the waste residue after treatment to about 0.60. Bai et al [119] also reported the influence of different acidification parameters, such as acid concentration, acidification temperature, and acidification time on the heat storage of calcium-based composites derived from steel slag. Among them, after the steel slag was acidified with acetic acid, the contents of Ca and Mg increased, while the contents of Si and Fe decreased, which improved its cyclic stability.…”
Section: Waste Cao-based Materialsmentioning
confidence: 99%
“…In the abovementioned acetic acid treatment process, a filtration step was added to remove silicon impurities, which could increase the effective conversion of the waste residue after treatment to about 0.60. Bai et al [119] also reported the influence of different acidification parameters, such as acid concentration, acidification temperature, and acidification time on the heat storage of calcium-based composites derived from steel slag. Among them, after the steel slag was acidified with acetic acid, the contents of Ca and Mg increased, while the contents of Si and Fe decreased, which improved its cyclic stability.…”
Section: Waste Cao-based Materialsmentioning
confidence: 99%